Uji Aktivitas Antiradikal Biji Pare (Momordica charantia L) Menggunakan Metode DPPH Serta Analisis Metabolit Sekundernya - Baiq Desy Ratnasari; Diah Miftahul Aini; Imam Syahputra Yamin; Gladeva Yugi Antari (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2022)
Momordica charantia L seed is classified as the domestic waste even though it has many health benefits, namely as anti-tumor, anti-virus, and as a medicine to increase the body resistance. Therefore, this study was designed to examine the antioxidant activity of the ethanol extract of the seeds using the DPPH method. Furthermore, a GC-MS analysis will be carried out to determine the chemical compounds that play a role in the bioactivity. Based on the absorbance of DPPH in three repetitions, the average value of DPPH inhibition by 95% ethanol extract of bitter melon seeds was 60.45%, in which classified as a good radical absorbance. The GC-MS results showed that the ethanol extract of bitter melon seeds contained ten chemical compounds consisting of sesquiterpenes, fatty acids, and alkanes, which affecting the radical absorbance of M. charantia extract.